New Synthesis of Vanillin by Degradation of Lignin in Presence of Functional Basic Ionic Liquid - Yi, Fengping; Jiang, Xiaoyan; Niu, Jihua; Zhang, Lirong; Wang, Zhen (Asian Journal of Chemistry, 2015)
The degradation of lignin catalyzed by functional basic ionic liquid was investigated. Higher conversion of lignin and simpler degradation product composition were obtained in the presence of basic ionic liquid, comparing with that under traditional NaOH solution. The reaction conditions were optimized. Ultrasound-assisted test proved that the ultrasound pretreatment favored the degradation process.